2018
DOI: 10.1111/ens.12319
|View full text |Cite
|
Sign up to set email alerts
|

Success of aphid parasitoids and their hosts varies with ant attendance: A field study

Abstract: Aphid–ant associations are often described as mutually beneficial interactions in which honeydew is traded for protection from predators and parasitoids. The aim of the present study was to determine parasitization avoidance in ant‐tended aphid colonies. Field experiments were carried out on two host plants: hoary cress Lepidium draba (Brassicaceae) and Canadian teasel Cirsium arvense (Asteraceae). Lepidium was host to Acyrthosiphon gossypii (Aphididae) tended by the ant Lasius turcicus (Formicidae) and attack… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 36 publications
1
2
0
Order By: Relevance
“…We did still observe some evidence for variation in ant responses to different L. fabarum lines (electronic supplementary material, figure S3 c ), and L. fabarum line 3 again elicited the lowest levels of aggression (electronic supplementary material, figure S3 and table S3). However, the failure to observe consistent differences in ant aggression toward L. fabarum lines versus the positive control ( A. colemani ) warrants significant caution in drawing conclusions about these results—because differential ant responses to these species are confirmed not only by other trials in the current study, but also by previous findings [56,57]. It seems likely that the high overall levels of ant aggression observed in this experiment are an artefact of our experimental conditions, and this interpretation is further supported by the divergent results observed for one wasp–aphid combination ( L. fabarum line 1 in A. gossypii ) that was tested in both this experiment and experiment 1: while this line elicited high levels of ant aggression (and no significant differences versus A. colemani ) in the current experiment, it elicited low levels of aggression (and strong differences from A. colemani ) across 52 replicates in experiment 1, as well as in preliminary experiments (not presented).…”
Section: Resultssupporting
confidence: 45%
“…We did still observe some evidence for variation in ant responses to different L. fabarum lines (electronic supplementary material, figure S3 c ), and L. fabarum line 3 again elicited the lowest levels of aggression (electronic supplementary material, figure S3 and table S3). However, the failure to observe consistent differences in ant aggression toward L. fabarum lines versus the positive control ( A. colemani ) warrants significant caution in drawing conclusions about these results—because differential ant responses to these species are confirmed not only by other trials in the current study, but also by previous findings [56,57]. It seems likely that the high overall levels of ant aggression observed in this experiment are an artefact of our experimental conditions, and this interpretation is further supported by the divergent results observed for one wasp–aphid combination ( L. fabarum line 1 in A. gossypii ) that was tested in both this experiment and experiment 1: while this line elicited high levels of ant aggression (and no significant differences versus A. colemani ) in the current experiment, it elicited low levels of aggression (and strong differences from A. colemani ) across 52 replicates in experiment 1, as well as in preliminary experiments (not presented).…”
Section: Resultssupporting
confidence: 45%
“…plantaginea on apple trees was high in the presence of ants and natural enemies activity was low compared to other apple trees without aphids. According to Sadeghi‐Namaghi & Amiri‐Jami (2018), ant attendance positively affected the population growth rate of the aphid species, Aphis ( Aphis ) gossypii , while other aphis species, Brachycaudus ( Prunaphis ) cardui was negatively affected by the presence of ants. The parasitism rate of A .…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the host preference or specificity of parasitoids on aphids is determined by the attending ants of the host aphids. Sadeghi-Namaghi and Amiri-Jami (2018) found that the parasitoid wasp Lysiphlebus fabarum successfully attacks the aphids Acyrthosiphon gossypii and Brachycaudus cardui attended by particular ant species. In another case, the parasitoid wasps Paralipsis eikoae and Aclitus sappaphis, respec-tively, attack the host aphid Sappaphis piri attended by the ants Pheidole fervida and Lasius niger (Takada and Shiga, 1974;Takada and Hashimoto, 1985;Akino and Yamaoka, 1998).…”
Section: Introductionmentioning
confidence: 99%